Holocene volcanic activity at Grímsvötn, Bárdarbunga and Kverkfjöll subglacial centres beneath Vatnajökull, Iceland - Oladottir, Bergrun; Larsen, G.; Sigmarsson, Olgeir (Bulletin of Volcanology, 2011)
International audience